1996
DOI: 10.1007/bf01799444
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal hypertrophic cardiomyopathy and pericardial effusion in carbohydrate‐deficient glycoprotein syndrome

Abstract: Background CLN3 disease is a major cause of childhood neurodegeneration. Onset of visual failure around 6 years of age is thought to precede cognitive deterioration by a few years, but casuistic reports question this paradigm. The aim of our study is to delineate timing of cognitive decline in CLN3 disease. Methods Early neurocognitive functioning in CLN3 disease was analyzed using age at onset of visual and cognitive decline and IQ scores from literature‐derived patient descriptions, supplemented with IQ scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Except for the risk of pericardial e †usion, the heart otherwise appears relatively spared in CDGS-I. Hypertrophic cardiomyopathy, as reported by others (Clayton et al 1992 ;Garcia Silva et al 1996 ;Harding et al 1988) was not found in our series of patients, except in one patient who displayed a slight asymmetric thickening of the septum.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Except for the risk of pericardial e †usion, the heart otherwise appears relatively spared in CDGS-I. Hypertrophic cardiomyopathy, as reported by others (Clayton et al 1992 ;Garcia Silva et al 1996 ;Harding et al 1988) was not found in our series of patients, except in one patient who displayed a slight asymmetric thickening of the septum.…”
Section: Discussionsupporting
confidence: 57%
“…Another case with hypertrophic obstructive cardiomyopathy was also reported (Clayton et al 1992). Prenatal diagnosis of hypertrophic cardiomyopathy and pericardial e †usion was recently described (Garcia Silva et al 1996). Otherwise the cardiovascular system has been noted to be normal (Harding et al 1988).…”
mentioning
confidence: 98%
“…Small testicular volumes with or without hypogonadism have been described . Other abnormalties include increased Follicle‐stimulating hormone (FSH), and cryptorchidism …”
Section: Systems Summaries and Statementsmentioning
confidence: 99%
“…The age of diagnosis of cardiomyopathy in reported cases ranged from the first week of life to 7 years of age, and in a few cases it was detected prenatally [2,25,31]. In addition, this is the first report of CDG from Saudi Arabia and it is likely that this condition is underdiagnosed in this region often due to poor access to appropriate metabolic and genetic testing.…”
Section: Discussionmentioning
confidence: 98%